HBV Subgenotype C2 Infection, A1762T/G1764A Mutations May Contribute To Hepatocellular Carcinoma with Cirrhosis in South-east China - Yueming Chen; Daojun Yu; Chunning Qiu; Guoqian Xiang; Weijian Dai; Shenghai Wu; Xianjun Wang (Tehran University of Medical Sciences, 2012)
Background: To glean insights into the relationship among hepatitis B virus (HBV) genotype/subgenotypes, A1762T/G1764A mutations and advanced liver disease such as liver cirrhosis (LC) and hepatocellular carcinoma (HCC) in Southeast China. Methods: A case-control study was performed, consisting of chronic hepatitis B (CHB) patients (n=160), LC patients (n=150), and HCC patients (n=156). Fluorescence quantitative polymerase chain reaction (FQ-PCR) was used to detect A1762T/G1764A mutations. HBV genotypes/subgenotypes were determined by multiplex PCR. All patients' clinical data was systematically collected from the hospital records. Results: Our study revealed HBV genotypes C (63.95%) and B (33.69%) were predominant in chronically infected patients, subgenotype B2, C2 and C1 were the major subgenotypes. Both subgenotype C2 infection and A1762T/G1764A mutations were associated with LC and HCC with cirrhosis, subgenotype C2 (OR=2.033, 95%CI=1.246-3.323, P=0.003 for LC vs CHB; OR=3.247, 95%CI=1.742-6.096, P=0.001 for HCC with cirrhosis vs CHB; respectively ), and A1762T/G1764A mutations (OR=1.914, 95%CI=1.188-3.085, P=0.005 for LC vs CHB; OR=2.996, 95%CI=1.683-5.353, P=0.002 for HCC with cirrhosis vs CHB; respectively), but no differences in the frequencies of both variants between LC and HCC with cirrhosis groups were found. Conclusions: HBV subgenotype C2 infection and A1762T/G1764A mutations are both risk factors of LC and HCC with cirrhosis development in the patients with CHB in Southeast China, but all no helpful for predicting HCC development in LC patients.